Motivational factors and structured input effects on the acquisition of English causative passive forms - Alessandro Benati; Mable Chan (Ampersand, 2023)
This study investigated the possible effects of motivational factors on the positive effects generated by structured input on the acquisition of English causative passive forms. This investigation builds upon the work carried out within the structured input research framework with the intention to measure online effects utilising a self-paced reading test. The self-paced reading test is a reliable measurement of language processing. Fifty Chinese (L1) subjects participated in the current study. They were all learning English in a university in the United Kingdom. After receiving two motivation questionnaires three groups were formed: structured input low-motivated (n = 15); structured input high-motivated (n = 20); and a control group (n = 15). Pre-tests and post-tests (immediate and delayed) were administered before and after the instructional treatment period which lasted for 3 h over a two-day period. The main findings from this experimental study confirmed the positive effects of structured input in facilitating the correct processing of English causative passive forms (accuracy and response time). The structured input activities groups improved equally from pre-to post-tests and they both retained the positive instructional effects over a 3-week period. Motivation was not a factor influencing the positive results generated by structured input. The present study contributes to the current call in the field for more empirical research to investigate the role of instruction and individual differences and the use of online tests to measure in-depth language processing.